Comparative study between transcervical extra-amniotic Foley’s bulb and prostaglandin E2 gel for pre-induction cervical ripening - Goswami, Prajakta; Annaldewar, Kapil; Giri, Deepali; Giri, Sachin (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Induction of labor is an artificial initiation of uterine activity before the spontaneous onset of labor with the aim of achieving vaginal delivery. Various pharmacological and non-pharmacological methods have been studied for the purpose. Methods: This randomized prospective study conducted in the Department of Obstetrics and Gynaecology at the Seth V. C. Gandhi & M. A. Vora Municipal General Hospital (Rajawadi Hospital), Mumbai from June 2019 to April 2020. It included pregnant patients admitted to the labor ward for induction of labor. A total 200 women were recruited and randomly allocated to the two study groups fulfilling the following selection criteria. Of these, 100 women were included in Foley's catheter group (group A) and 100 in (group B) prostaglandin E2 (PGE2) group. Results: The subjects included mainly were of 24-28 years age group. The period of gestation was 37-42 weeks in majority of the women in both the groups. Maximum numbers of women in both groups were primigravidae, being 66% in group A and 70% in group B. Foley catheter proved to be a highly effective pre-induction ripening agent for unfavorable cervix, compared to PGE2 gel, as evident by the mean Bishop score at 12 hours (p<0.05) and by the difference in change of Bishop score over 12 hours (p<0.05) in both groups A and B. Women in both the groups had a high rate of normal vaginal delivery, rate being significantly more in Foley’s group. Conclusions: This study concludes that extra-amniotic Foley’s catheter balloon is an effective, safe, simple, low cost, reversible, non-pharmacological mechanical method of pre-induction cervical ripening.